Improving the handling of NCD using ISM to achieve operational efficiency / Muhammad Hafiz Fazlil - Fazlil, Muhammad Hafiz (Faculty of Business and Management, Universiti Teknologi MARA, 2010)
ISM was conceptualized in 1998 by the General Insurance Association of Malaysia (PIAM) as the Malaysian Insurance Rating Organization (MIRO) project. The objective of MIRO was to put in place databases to support pricing and reserving in a liberalized pricing environment. The project took shape in 2000 when PIAM established the MIRO department and employed an actuarial manager to coordinate the project. In July of 2003, the PIAM management committee decided to merge the MIRO and MIS departments to become the ISM department. The scope for the project was also expanded to include anti-fraud and Information Technology related services. Takaful operators began to participate and contribute data to ISM in 2003. This was followed by life companies in 2004. The PIAM management committee recognized the need to create a separate entity to enable ISM to carry out its role more effectively and also formally involve the Takaful and life insurance industry. On the 18th of February 2005, ISM was incorporated as a company limited by guarantee with 35 insurers and 4 Takaful operators as members. ISM commenced operations on 1 April 2005.